Comparison of 11C-L-methionine uptake by the parotid gland and pancreas in chronic pancreatitis studied by positron emission tomography. Issue 7 (July 1983) - Syrota, A; Collard, P; Paraf, A
Abstract : L-methionine uptake by the parotid gland and pancreas has been compared in 27 patients using a non-invasive methodology. L-methionine was labelled with 11C, a positron emitter with a short half life produced in a cyclotron. 11C-L-methionine concentration was measured in the parotid glands and in the pancreas by external detection using a positron emission tomographic system. 11C-L-methionine uptake by the parotid glands was 4.3 X 10(-3) +/- 1.9 X 10(-3)% of the injected dose per millilitre of tissue (mean +/- SD) in a group of 11 normal non-alcoholic subjects. The uptake was 3.6 +/- 1.3 (X10(-3) in a group of nine alcoholic subjects without pancreatic disorder and it was 4.9 +/- 1.5 (X10(-3) in a third group of seven patients with chronic pancreatitis. These values did not significantly differ. In contrast median pancreatic uptake of 11C-L-methionine was nil in chronic pancreatitis and was lower than that seen in normal subjects (15.3 X 10(-3)% ml, p less than 0.001) and in alcoholic subjects (11.5 X 10(-3)% ml, p less than 0.002). Thus neutral long chain amino acid transport in the parotid gland appears to be independent of that in the exocrine pancreas in chronic pancreatitis. This absence of relationship between the parotid gland and the pancreas in pancreatic disease is in contradiction with the demonstration made in animals of an interaction between these two glands. These results, however, are in agreement with the conclusions drawn from the data collected from the saliva test used by several authors.